LITERACY INCLUSION IN REALIZING DISABILITY-FRIENDLY LIBRARY SERVICES: A NARRATIVE LITERATURE REVIEW - Zevyla Azaleia Mintarso; Zulfatun Sofiyani (Departemen Sastra Indonesia, Fakultas Sastra, Universitas Negeri Malang (UM), 2024)
Abstract: People with disabilities find it difficult to live independently and work like the general public. The lack of public service facilities, especially libraries, has not been able to provide easy access to literacy resources. The presence of literacy inclusion in library services is an effort to create a library environment that is friendly to people with disabilities. The purpose of this study is to find out how literacy inclusion can be a foundation for libraries to meet the needs of people with disabilities and develop services that are in accordance with the principles of inclusion. The research method uses narrative literature review. The results of this study underscore the complexity of literacy inclusion in the library context and view it as a concept that involves not only technical and service aspects, but also community engagement, identity formation, inclusive pedagogy, and advocacy.